A single-sided meandered-dual-antenna structure for UHF RFID tags. Issue 7 (4th April 2017) - Kamalvand, Pouria; Pandey, Gaurav Kumar; Meshram, Manoj Kumar
Abstract : A meandered-dual-antenna structure is proposed for UHF radiofrequency identification (RFID) tag. It is composed of two independent antennas printed on the one side of the substrate board. One of the antennas is exclusively used for receiving and harvesting sufficient energy to the tag chip having the complex conjugate impedance of the receiving antenna. The other is for backscatter to enhance maximum differential radar cross-section with purely real input impedance, to enhancement the read range. The receiving antenna is formed by a rectangular loop and a parasitic meandered line. The rectangular loop is used as a feeding element for the meandered line. The backscattering antenna is made using a meandered dipole along with a thin rectangular strip. The input impedance of the receiving antenna is designed to be conjugate matched to the chip impedance (13.5-j110 Ω), whereas the input impedance of backscattering antenna alternatively switched to open and short circuit for modulating the backscattered field. The input impedance of receiving and backscattering antennas is measured using differential probe technique. The simulated and measured results are found in good agreement. It is also demonstrated that the read range of UHF RFID system increased considerably by using the dual-antenna structure.